Assessment of suicidal risk factors in young depressed persons with non-suicidal self-injury based on an artificial intelligence - Xuanyan Zhu; Yun Chen; Zhongyi Jiang; Ran Bi; Qiaoyang Zhang; Yanli Chen; Yupeng Jiang; Yin Cao; Guanzhong Dong (BMC Psychology)
Abstract Introduction The role of non-suicidal self-injury (NSSI) in the suicide process of people with major depressive disorder(MDD) remains controversial. Therefore, the purpose of this study was to investigate the role NSSI plays in suicide risk in people with MDD. Methods A questionnaire survey was compiled using the Hamilton Depression Scale-24, the Baker Suicide Risk Scale, and the Deliberate self-harm Scale. The correlation between NSSI, depression, and suicide risk was analyzed using the gradient-lifting regression model. Results A total of 179 people with MDD aged 15–24 years were included in this study. NSSI had the highest incidence among high school students(63.3%), regardless of sex. Furthermore, the incidence of NSSI was high among patients with depression with a history of smoking(p < 0.0002) and drinking(p < 0.001). NSSI partially mediated the risk of suicide in people with depression. Conclusion The findings demonstrate a significant association between NSSI and elevated suicide risk scores in individuals with MDD, with NSSI acting as a partial mediator in this relationship.